THE VOCABULARY MASTERY OF THE SECOND SEMESTER STUDENTS OF WIDYA DHARMA UNIVERSITY IN ACADEMIC YEAR 2015/2016 - Anisa, Ike (MAGISTRA, 2016)
As the basic component of the four language skills, vocabulary has to be mastered by thelearners. Vocabulary is the main point to learn English. Without it a student will get difficulty to learn English. Inthe early semester, vocabulary is the first step to learn English. By knowing the vocabulary from the beginningthe students will get a lot of knowledge and will not get difficulties in mastering language skills. Thus, vocabularyshould be on the first priority in the English language teaching and learning.Vocabulary mastery has always been an essential part of English as foreign language. There is no doubtthat vocabulary mastery plays an important role in the four language skills. They are listening, speaking, reading,and writing. All four aspects are interrelated. But before students master all aspects, they must master vocabularyfirst. Vocabulary must not be neglected by anyone who learns English. From the importance of vocabularyabove, teacher should give serious attention in teaching vocabulary.In this research, researchers would like toanalyze the studentsâ vocabulary ability entitled âThe Vocabulary Mastery of The Second Semester Students ofWidya Dharma University in 2015/2016â.In this research, researchers conducting descriptive study to answer the question on how is the vocabularymastery of the second semester students of Widya Dharma University in 2015/2016. Thus, the researchersfound that the vocabulary mastery of the students is categorized into good.Keyword : vocabulary, vocabulary mastery, good.